Atheists, Agnostics, Spirituals, and Christians: Assessing Confirmation Bias within a Measure of Cognitive Ability - Yancey, George (Research in the social scientific study of religion, 2014)
Empirical evidence indicates that nontheists have higher levels of cognitive abilities than religious individuals, but previous research fails to account for possible ideological effects in cognitive ability measures. This article explores how ideological presup-positions potentially confound attempts to correlate religious beliefs to cognitive assessments. A revised version of Altemeyer’s test of logical fallacies, including statements testing the conceptual assumptions of atheists, assesses whether the ability of atheists to overcome confirmation bias is higher than that of Christians. Agnostics and spiritual but not religious individuals were also included to assess individuals with differing levels of commitment to ideologies of atheism and Christianity. Atheists fail to accurately answer questions challenging their presuppositions followed in accuracy by agnostics, spirituals but not religious, and Christians. This order is reversed on statements that challenge the presuppositions of Christians. Findings suggest that previous assertions of the cognitive superiority of the nonreligious may reflect ideological bias within the testing measures instead of an innate cognitive ability difference.